The Trade-off between Intra- and Intergenerational Equity in Climate Policy - Snorre Kverndokk; Eric Nævdal; Linda Nøstbakken (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper focuses on two equity dimensions of climate policy, intra- and intergenerational equity, and analyzes the implications of equity preferences on climate policy, and on the production and consumption patterns in rich and poor countries. We develop a dynamic two-region model, in which each region suffers from local pollution and global warming, but also has an inequality aversion over current consumption allocations. Inequality aversion lifts the consumption path of the poor region, while the rich region must take a greater share of the climate burden. Furthermore, with inequality aversion, the optimal climate policy leads to higher investment in clean capital in the North and in dirty capital in the South, thereby allowing the South to pollute more and develop faster. The optimal policy may even require the poor region to increase emissions relative to the uncoordinated business-as-usual case. Introducing transfers between the regions reinforces these effects. However, loans to poor countries to reduce inequality may result in a debt crisis, and hence, debt remittance may be part of the optimal climate policy.
Keywords: C63; D31; D63; Q54; 330; intragenerational equity; intergenerational equity; inequality aversion; climate policy; economic development; international transfers; debt crisis